Understanding the epigenetic origins of congenital heart disease may lead to its control - De Decker, Rik (SA Heart Journal, 2017)
Congenital heart disease (CHD), which occurs in about 1 per 100 live births, remains the leading life-threatening abnormality present at birth. It is reasonable to assume that most, if not all, CHD stems from errors or disruptions in the genetic control of heart development, and that a more thorough knowledge of these controlling molecular mechanisms may lead to a better understanding of the origins of CHD. With understanding comes the potential for prevention, and possibly early repair. Our operational research in the Western Cape has identifi ed a severe epidemiological shortfall between the theoretical number of newborns that should present to us with severe CHD and those who actually do - we are referred only 50% of the children that (epidemiologically) should receive heart surgery. Even if we could identify all the missing children, our services would be unable to contend with the consequent demand. This stark dilemma plays itself out in most resource-constrained cardiac health services. It is therefore of utmost importance that the origins of CHD that may be under environmental infl uences - “the epigenetic causes of CHD” - are prioritised in our quest to reduce heart defects. I will outline these infl uences and show how an understanding of them may begin to reduce an enormous health burden.